Synergistic functional properties of hydroxypropyl-modified starch and iota carrageenan for plant-based soft capsule shells: Sifat fungsional sinergis modifikasi pati hidroksipropil dan iota karageenan untuk kulit kapsul lunak berbasis tumbuhan - Hidayat, Taufik; Syamsu, Khaswar; Nurilmala, Mala; Manalu, Lamhot Parulian; Perwatasari, Dayu Dian; Ramlan, Ramlan; Putri, Renny Primasari Gustia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Soft capsules are widely used oral dosage forms; however, the reliance on gelatin has raised safety, religious, and ethical concerns, driving the need for plant-based alternatives. Starch, a biodegradable and renewable polysaccharide, is a promising candidate; however, it suffers from poor solubility, retrogradation, and instability under acidic or thermal conditions. Chemical modification, particularly hydroxypropylation, has been employed to overcome these drawbacks, and iota carrageenan offers additional benefits as a gelling agent that enhances elasticity and stability. This study aimed to determine the best functional and thermal properties of hydroxypropyl derivatives from cassava, sago, corn, and potato, and to examine their potential for soft capsule application. This study characterized various hydroxypropyl starch modifications and determined the characteristics of the modified starch that meet the raw material requirements for soft capsule shells using the Zeleny method. The analysis parameters included degree of substitution, water holding capacity, oil holding capacity, swelling power, solubility, pasting properties, differential scanning calorimetry, scanning electron microscopy, Fourier Transform Infrared Spectroscopy, iota carrageenan, and rapid visco analysis. The results showed that hydroxypropyl cassava starch exhibited selected mechanical properties, with a DS value of 0.104, WHC of 4.21%, OHC of 5.43%, swelling of 24.23%, and solubility of 21.54%. Hydroxypropylation improved the solubility, thermal resistance, and water retention, with cassava starch exhibiting the highest degree of substitution and favorable film-forming ability. Furthermore, incorporating iota carrageenan into hydroxypropyl cassava starch generated homogeneous composite films with enhanced mechanical strength and stability. These findings highlight the synergistic potential of hydroxypropyl starch and iota carrageenan, providing a scientific basis for developing sustainable, plant-based soft capsule shells as viable alternatives to gelatin.